Can tree leaves be used as an alternative source of synthetic antioxidants? Use of jujube leaf extract in laying hens - Kılınç, Gözde (Frontiers in Veterinary Science, 2023)
This study was carried out to determine the antioxidant activity of jujube (Zizyphus jujuba Mill.) leaf extract (JLE) and to evaluate the effects of its use as an extract in laying hen diet (Nick Brown; 32 weeks old) on performance, egg quality and lipid peroxidation. A total of 4 groups (24 replicates/group), one control (JLE-0) and three experimental groups (JLE-1, JLE-2, JLE-3), were formed and the hens were individually distributed in cages. The groups were fed with 0, 45, 90 and 135 mg/kg extract, respectively. The total phenolic content of the extract was 118.60 g gallic acid aquivalent/kg (GAE/kg) and the IC50 value was determined as 332.01 as a result of the DPPH (2, 2- diphenyl- 1 -picrylhydrazyl) free radical scavenging activity assay. Performance parameters except for feed conversion ratio (FCR) were not affected by the extract in the diet. Compared to the control group, FCR decreased (P<0.05) and feed conversion improved in all experimental groups. The linear effect was significant for egg production (EP) (P<0.05). Furthermore, egg quality parameters except for the albumen index (AI), Haugh unit (HU), shell weight (SW), and shell thickness (ST) were not affected by the extract in the diet. The highest AI and HU were in the JLE-2 group (P<0.05). Besides, SW was found to increase in all experimental groups (P<0.001). The highest ST was in JLE-1 (P<0.001). The addition of the extract was found to slow down lipid oxidation by decreasing Thiobarbituric Acid Reactive substances (TBARs) levels on days 0 and 28 (P<0.05). In conclusion, JLE can be used as a natural extract in laying hen diets.